Pengetahuan Penyakit Pernapasan Kronik pada Perokok Aktif - Laksono, Pandu; Suryadinata, Rivan Virlando; Lorensia, Amelia (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
Cigarettes are one of the addictive substances in the form of nicotine, which can cause dependence for the wearer.In Indonesia, the number of smokers continues to increase every year. The prevalence of adult smokers consistedof men (67.4%), women (4.5%) from 36.1% of the population. The mortality rate due to smoking is expected tocontinue to increase because there is a significant relationship between the degree of smoking and the severity ofCOPD. COPD is a disease that attacks the lungs, one of the causes of which is cigarette smoke. The higher the levelof knowledge of active smokers, the lower the risk of a person getting COPD. Therefore, research is neededregarding the level of knowledge of chronic respiratory diseases related to active smokers. This study aims todetermine the level of knowledge of chronic respiratory disease in active smokers in Pungging Mojokerto District.The method used is a quantitative cross-sectional design with purposive sampling and analyzed descriptively. Theresults showed that the level of knowledge of active smokers in the District of Pungging Mojokerto on chronicrespiratory disease there are 3 levels of categories. Of the three categories, the highest level of knowledge wasobtained in the moderate category (50.82%), high category (44.26%), and low category (3.28%).